Combination immunotherapy: Where do we go from here?. Issue 1 (18th August 2015) - Overacre, Abigail E.; Kurtulus, Sema; Sznol, Mario; Pardoll, Drew M.; Anderson, Ana; Vignali, Dario A. A.
Abstract : The remarkable clinical success of cancer immunotherapies targeting the checkpoint receptors CTLA-4 and PD-1 has generated considerable excitement and emboldened efforts to build on this important foundation. Research efforts are now focused on understanding the mechanism of action of these immunotherapies, identifying new inhibitory mechanisms that could be targeted to achieve responses in patients with refractory cancers, and developing approaches that might exhibit efficacy against "immunologically inert" tumors. The outstanding challenges in moving forward are developing reliable strategies for determining which patients will respond optimally to a given immunotherapy, and what combination of immunotherapies and conventional therapies will prove beneficial against each tumor type. These issues were discussed in a one-day workshop at the SITC meeting in November 2014.